Salient beliefs, preferences and intention to use HIV pre- exposure prophylaxis among pregnant and breastfeeding women in Zambia - Hamoonga, Twaambo Euphemia (University of the Witwatersrand, Johannesburg, 2024)
Pregnant and breastfeeding women living in sub-Saharan Africa are at substantial risk for HIV infection, and maternal seroconversion may affect the quality of life for the mother, and is a risk for vertical transmission of HIV. Despite the adoption of PrEP into national guidelines for HIV prevention, its uptake in antenatal and postnatal settings in Zambia remains low. We used an exploratory sequential mixed methods design to explore facilitators and barriers to uptake of PrEP among pregnant and breastfeeding women (18 years or older) not living with HIV in Zambia. We purposively recruited 24 women for the qualitative component and conveniently selected 389 women for the quantitative component of the study at Chipata Level 1 Hospital in Lusaka. For qualitative data, Nvivo was used for data management and data was analysed using thematic analysis. Quantitative data was analysed using chi-square test, pearson correlation coefficient (r) and logistic regression analysis using Stata v.16. Findings from our qualitative study showed that women had positive attitudes and favourable intentions to use PrEP. Most women felt that people who are important to them, especially their male partners, would not support PrEP use during pregnancy and breastfeeding. The anticipated disapproval from partners made women believe that PrEP use would not entirely be under their control, with some reporting that they would not use PrEP if their partners disapproved. Women also cited rude health care provider attitude as a potential barrier to uptake. Some women preferred receiving PrEP from a health facility for fear of stigma in the community while others preferred community-based delivery as an avenue for creating PrEP awareness. This paper was published in Frontiers in Reproductive Health In our second paper, we determined intention to use PrEP during pregnancy and breastfeeding and also identified salient beliefs associated with it. Participants had positive attitude and favourable intention to use PrEP during pregnancy and breastfeeding (mean = 6.65, SD = 0.71 and mean = 6.01, SD = 1.36), respectively. They felt that people who are important to them would approve of their use of PrEP (mean = 6.09, SD = 1.51) and also believed that they would be able to use PrEP if they desired (mean = 6.52, SD = 1.09). All salient beliefs positively and significantly predicted intention to use PrEP during pregnancy and breastfeeding: attitude (β = 0.24, p<0.01); subjective norms (β = 0.55, p<0.01); and perceived behavioural control (β = 0.22, p < 0.01). This paper was published in Global Public Health. The third paper discusses findings from a discrete choice experiment (DCE) on preferences for PrEP service delivery among pregnant and breastfeeding women. In this study, waiting time, travel time, health care provider attitude and amount of PrEP supply at each refill were important considerations likely to influence PrEP use during pregnancy and breastfeeding (all p<0.01). Women expressed strong preference for 3-month’s supply of PrEP compared to other attribute levels (β= 1.69, p<0.01). They were willing to wait for 5 hours at the facility, walk for more than an hour to a facility dispensing PrEP, encounter a health care provider with a negative attitude as long as they received PrEP enough for 3 months. This paper is under review in Frontiers in Reproductive Health. The overall contribution of this PhD research to the body of knowledge on HIV prevention strategies is the ability to identify beliefs about PrEP and how each salient belief influences intention to use PrEP during pregnancy and breastfeeding. It is also one of the first to estimate the benefit (value or satisfaction) that women derive from different attributes of PrEP service delivery for pregnant and breastfeeding populations interested in using PrEP. This information could provide guidance on specific beliefs and service delivery attributes of PrEP that women prefer the most and therefore need to be prioritized if PrEP uptake is to improve in antenatal and postnatal settings
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements for the degree of Doctor of Philosophy in Public Health (HIV and Women’s Reproductive Health),Witwatersrand, Johannesburg 2024
Keywords: Pregnant and breastfeeding wome; HIV infection; PrEP; UCTD; SDG-3: Good health and well-being